If it's not what You are looking for type in the equation solver your own equation and let us solve it.
40+5x=4(-x+3)-44
We move all terms to the left:
40+5x-(4(-x+3)-44)=0
We add all the numbers together, and all the variables
5x-(4(-1x+3)-44)+40=0
We calculate terms in parentheses: -(4(-1x+3)-44), so:We get rid of parentheses
4(-1x+3)-44
We multiply parentheses
-4x+12-44
We add all the numbers together, and all the variables
-4x-32
Back to the equation:
-(-4x-32)
5x+4x+32+40=0
We add all the numbers together, and all the variables
9x+72=0
We move all terms containing x to the left, all other terms to the right
9x=-72
x=-72/9
x=-8
| X*3x=6689 | | -6x+20x=20x-1 | | 3(4-4y)=18-9y | | u/2+4=10 | | 39*x^2+12*x-4=0 | | 4-3x=32+4x | | -14=2w-2 | | 10=5+w/5 | | x-40=2x+10 | | 4*x+9=41 | | 4x+3=1x-3 | | (x)=0,13x(3)-2.8x(2)+23x+52 | | 3(q+34 )=2 | | X2+20x=25 | | 4x-6-8x-9=20 | | 24=v/5-14 | | 3x-3-5x=10+8x+7 | | -3x-4=4(x+2.5) | | 6/5=14/x | | 9x+50=4x+110 | | 5/8t=1/2 | | x-44=43 | | x+40=72 | | 13-5x=13x-140 | | x-39=52 | | 3(2x-4)+3x=-3(x-8) | | -6.5+x=18.7 | | 1+8x=11+2x | | 9-(x+6)=4x-2 | | 2(x+5=3x+1 | | 6x-2=1/2x+9 | | 4(3n-5)=12n-20 |